Acacetin—A simple flavone exhibiting diverse pharmacological activities. (August 2019) - Semwal, Ruchi Badoni; Semwal, Deepak Kumar; Combrinck, Sandra; Trill, Jeanne; Gibbons, Simon; Viljoen, Alvaro
Graphical abstract: Highlights: Acacetin is an abundant flavone produced by many species. A plethora of bioactivities have been confirmed for this flavone. Anticancer and enzyme inhibition assays are most promising. Several commercial products have been developed. Abstract: Acacetin (5, 7-dihydroxy-4-methoxyflavone) is a naturally occurring flavonoid, known to possess numerous pharmacological properties, including neuroprotective, cardioprotective, anticancer, anti-inflammatory, antidiabetic, and antimicrobial activities. The molecule is widespread throughout the Plant Kingdom, but is particularly abundant in the Asteraceae, Euphorbiaceae, Passifloraceae, Lamiaceae and Malvaceae families. It has been shown to exhibit strong inhibitory effects against glutathione reductase, cyclo-oxygenase, acetylcholinesterase, aldose reductase and xanthine oxidase enzymes. A comprehensive overview of the potential therapeutic applications of acacetin was prepared after collating selected peer-reviewed papers, accessed from online scientific databases, specifically PubMed, Web of Science and Scopus. The mechanism of action, dose forms and structure-activity relationships of the molecule are some of the aspects discussed in the review, to facilitate further research and use of this molecule.